Design and Characterization of the Multi-Band SWIR Receiver for the Lunar Flashlight CubeSat Mission - Quentin Vinckier; Luke Hardy; Megan Gibson; Christopher Smith; Philip Putman; Paul O. Hayne; R. Glenn Sellar (Remote Sensing, 2019)
Lunar Flashlight (LF) is an innovative National Aeronautics and Space Administration (NASA) CubeSat mission that is dedicated to quantifying and mapping the water ice harbored in the permanently shadowed craters of the lunar South Pole. The primary goal is to understand the lunar resource potential for future human exploration of the Moon. To this end, the LF spacecraft will carry an active multi-band reflectometer, based on an optical receiver aligned with four high-power diode lasers emitting in the 1 to 2-μm shortwave infrared band, to measure the reflectance of the lunar surface from orbit near water ice absorption peaks. We present the detailed optical, mechanical, and thermal design of the receiver, which is required to fabricate this instrument within very demanding CubeSat resource allocations. The receiver has been optimized for solar stray light rejection from outside its field of view, and utilizes a 70 × 70-mm, aluminum, off-axis paraboloidal mirror with a focal length of 70 mm, which collects the reflected light from the Moon surface onto a single-pixel InGaAs detector with a 2-mm diameter, hence providing a 20-mrad field of view. The characterization of the flight receiver is also presented, and the results are in agreement with the expected performance obtained from simulations. Planned to be launched by NASA on the first Space Launch System (SLS) test flight, this highly mass-constrained and volume-constrained instrument payload will demonstrate several firsts, including being one of the first instruments onboard a CubeSat performing science measurements beyond low Earth orbit, and the first planetary mission to use multi-band active reflectometry from orbit.